Associação entre doses elevadas de ácido fólico com ativação de linfócitos T, B e NK e suas possíveis consequências no processo inflamatório em indivíduos saudáveis - Lucena, Maylla Rodrigues [UNIFESP] (2019)
BACKGROUND:Folate is a B-complex vitamin withanimportantrole on cell replication since its involvement in DNA and RNA synthesis. In Brazil, most pharmaceutical formulationsof folic acid (FA) taken by women who intend to get pregnant and hemolytic anemia patients contain 5 mg, which is higher than tolerable upper intake levelof this vitamin for healthy subjects. Currently, there is a concern about intake of high doses of FA, once high consumption of FA has been associated to higher folate concentrations on the body, as well as appearanceof an unmetabolized fraction (UMFA). Elevated concentrations of folate and UMFA seem to be implied with changes on immunity. AIM: To assess the association between high doses of FA intake with activation of T, B and NK lymphocytes, and to investigate the possibleimplications in the inflammatory process in healthy individuals.METHODS:34healthy subjects make use of 5mg/day of FA during 90 days. Blood samples were collected at baseline and after 45 and 90 days of FA use. It was assessed: serum and RBC folate, UMFA and other folate forms; vitamin B12; T, B and NK cell activation assays; serum concentrations of interleukin (IL)-6, IL-8, IL-10, interferon gamma (IFN-γ) and tumor necrosis factor alpha (TNF-α).RESULTS:Higher serum and RBC folate, UMFA and 5-methyltetrahydrofolate concentrations were observed after 45 and 90 days of FA use when compared to baseline. Number of T CD4+ cellsincreased, and T CD8+ cells decreased after 90 days of FA use regarding to baseline and 45 days. After 90 days, decreased number of B cells/HLA-DR+ and NK cells/CD38+ after PMA and ionomicin stimulation were observed.CONCLUSIONS:Intake of 5 mg/ day of FA by healthy individuals was associated to increased circulating concentrations of folate, as well as increased number of T CD4+ cells and decreased T CD8+ cells. In addition, our data show relation between FA use and decrease on B and NK cells activation.